KLASIFIKASI AROMA KULIT KUDA DAN KULIT BABI MENGGUNAKAN ELECTRONIC NOSE (e-Nose) - Saputra, Rakha; Putri, Desrinda Mala Dwi; Rakhmadi, Frida Agung; Hidayat, Shidiq Nur; Triyana, Kuwat (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
Electronic nose (e-Nose) has successfully classified the aroma of horse hide and pigskin. The sensor used by e-Nose consists of eight Taguchi Gas Sensor (TGS) sensors. This study uses a baseline reduction and feature extraction method with an average maximum value. The classification results between the two skins are shown by a graph plot. There is one TGS which shows no difference between the smell of horse skin and pork rind. The other TGS responds and shows the difference between the two skin scents.